Relationship between the Cognition and Fear of Fall among Elderly People - Pavithra, Venugopal; Suganya, Murugesan; Ranjeetha, Ravichandran; Yughdtheswari, Muniandy; Vinosh Kumar, Purushothaman (INTI International University, 2023)
Background: Aging is a dynamic process that varies from one individual to another and is marked by a reduction in physiological function. With changes caused by aging, it becomes more difficult to maintain balance because motor function involves an interaction of information from visual, vestibular, and proprioceptive systems that are integrated in the central nervous system. These functional changes may predispose the elderly to balance problems and increase the likelihood of falling. The Aim and Objective of the present study was to evaluate the relationship between Cognition and Fear of Fall among elderly people. Methodology: A correlation study that includes40 subjects with both genders and mean age of 58.7 ± 4.57 were conducted. Participant’s cognitive function and fear of fall were assessed using Mini-Mental State Examination and Activity-specific Balance Confidence Scale. The data were analyzed during Pearson Correlation Coefficient. Results showed that there was a positive correlation between Cognition and Fear of Fall among elderly peoples (r=0.8967, p> 0.01). Conclusion: The study concludes that older adults with possible cognitive decline have lower balance confidence, and greater fear of falling which address the needs of early attention in the management of falls.